Post-Human Perspectives on Film: Exploring Innovative Applications of AIGC (应用人工智能研究, 2026)
The advent of AIGC(Artificial Intelligence Generated Content) represents a silicon-driven revolution for the carbon-based era of cinema. Human approaches to filmmaking have evolved—from celluloid to digital, from handwritten scripts to computer-generated texts—and are now increasingly oriented toward the development and collaboration with AIGC. During the process of employing AIGC in film production, it has become deeply embedded in cinematic art, whether through the secondary creation of celluloid imagery, collaborative brainstorming with humans, or integration with VR to craft new and enhanced viewing experiences. This study demonstrates that AIGC can significantly enhance the efficiency and creativity of film production, offering innovative solutions for image restoration, facilitating seamless human–machine collaboration, and enabling immersive VR-based cinematic experiences. By systematically analyzing these applications, the research provides a framework for understanding the transformative impact of AIGC on contemporary cinema and highlights its potential to redefine aesthetic and production standards in the film industry.